Developing Heterologous Expression Platforms for the Production of Polyketides from Microbial Hosts - Stevens, David Cole (Université d'Ottawa / University of Ottawa, 2011)
Bacterial polyketides possess an enormous range of chemical diversity and biological function. Many polyketides such as tetracycline, epothilone, and rapamycin have been developed into key clinical pharmaceuticals in a broad range of therapeutic areas. Sequencing of bacterial genomes has shown that there are many more polyketide biosynthetic pathways than there are polyketides isolated from standard cultivation techniques. These genetically encoded polyketide natural products from cultivatable and uncultivatable bacteria represent one of the greatest remaining untapped reservoirs of new natural product diversity. To access this untapped diversity of polyketide products, a general method for heterologous expression of these pathways is needed. Heterologous expression has proven to be a valuable asset in the discovery, production, engineering, and characterization of bacterial secondary metabolites and the complex enzymology involved in their biosynthesis. Herein we discuss the development and investigation of two unique heterologous expression platforms utilizing host strains of Myxococcus xanthus and Escherichia coli. Using our developed heterologous hosts, we were able to produce the Streptomyces rimosus polyketide oxytetracycline. Through production of oxytetracycline in E .coli we have identified the potential of alternative transcription factors as regulators of secondary metabolism. Further investigation and development of alternative transcription factors as regulators of secondary metabolism in heterologous hosts could benefit the development of robust general methodology for the heterologous expression of polyketides.
Keywords: Heterologous Expression; Polyketide; Sigma54; Oxytetracycline